Influence of a vented mouthguard on physiological responses in handball - Schulze, A.; Laessing, J.; Kwast, S.; Busse, M. (The Journal of Strength and Conditioning Research, 2020)
However, airway obstruction and a resulting decrease in performance are theoretical disadvantages regarding their use. The study aim was to assess possible limitations of a "vented" MG on aerobic performance in handball. The physiological effects were investigated in 14 male professional players in a newly developed handball-specific course. The measured values were oxygen uptake, ventilation, heart rate, and lactate. Similar oxygen uptake (VO2) values were observed with and without MG use (51.9 ± 6.4 L/min·kg vs. 52.1 ± 10.9 L/min·kg). During maximum load, ventilation was markedly lower with the vented MG (153.1 ± 25 L·min-1 vs. 166.3 ± 20.8 L·min-1). The endexpiratory concentrations of O2 (17.2 ± 0.5% vs. 17.6 ± 0.8%) and CO2 (4.0 ± 0.5% vs. 3.7 ± 0.6%) were significantly lower and higher, respectively, when using the MG. The inspiration and expiration times with and without the MG were 0.6 ± 0.1 seconds vs. 0.6 ± 0.1 seconds and 0.7 ± 0.2 seconds vs. 0.6 ± 0.2 seconds (all not significant), respectively, indicating that there was no relevant airflow restriction. The maximum load was not significantly affected by the MG. The lower ventilation for given VO2 values associated with MG use may be an effect of improved biomechanics and lower respiratory drive of the peripheral musculature.